2015
DOI: 10.1039/c5tb00251f
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear iridium(iii) complexes as phosphorescent trackers to monitor mitochondrial dynamics

Abstract: 5Mitochondria dynamic processes are essential for mammalian development and engaged in several diseases. However, commercial mitochondrial probes are currently too limited to satisfactorily track these dynamics. In this present work, seven dinuclear iridium(III) complexes [(ppy) 2 Ir(L 1-7 )Ir(ppy) 2 ] 2+ (Ir1-Ir7, ppy = 2-phenylpyridine, L = 1,3-bis(1-substituted-1H-imidazo[4,5-f][1,10]phenanthroline-2-yl)benzene) were synthesized. Possessing high specificity to mitochondria, low cytotoxicity and high resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…These processes are involved in the remodeling of mitochondrial cristae and the mobilization of cytochrome c, which is considered an irreversible process associated with the collapse of the membrane potential 39. Similar results were observed when we used IrL1 , IrL3 , IrL4 and IrL5 to conduct this experiment (Figures S32–S35 in the Supporting Information), which is consistent with previous results from our laboratory with similar complexes 16c…”
Section: Resultssupporting
confidence: 91%
“…These processes are involved in the remodeling of mitochondrial cristae and the mobilization of cytochrome c, which is considered an irreversible process associated with the collapse of the membrane potential 39. Similar results were observed when we used IrL1 , IrL3 , IrL4 and IrL5 to conduct this experiment (Figures S32–S35 in the Supporting Information), which is consistent with previous results from our laboratory with similar complexes 16c…”
Section: Resultssupporting
confidence: 91%
“…For comparison, several ditopic chelates linked via pyrimidine, pyrazine and pyridazine, or functional 2‐phenylpyrimidine, diarylhydrazide, isocyanate, terpyridine dicarboxylate, and oxamidato based bridging ligands have been employed in the preparation of charge‐neutral luminescent diiridium complexes ( 5 – 8 ) ( Scheme ). Also, the bridging entities with iminopyridine, dipyridylpyrazine, and phenanthroline were found useful in making the cationic dinuclear Ir(III) complexes. Despite that the majority of these complexes have exhibited excellent luminescence versus representative di‐iridium complexes reported earlier, fabrication of OLED using the same is limited to the solution processes due to the poor volatility.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most important cell signaling center, mitochondria are essential organelles required for cellular energy production and are involved in many other cellular activities, one of which is to produce reactive oxygen species (ROS) and leads to mitochondria-mediated apoptosis [19][20][21]. Our previous works showed that mitochondria is the main target of cyclometalated iridium(III) complexes [22][23][24][25][26][27]. Herein, four novel cyclometalated iridium(III) complexes were developed as mitochondria-targeted theranostic agents.…”
Section: Introductionmentioning
confidence: 99%